Pengembangan Interpretasi Wisata Budaya Guna Mendukung Program Pelestarian Tapak Arkeologi - YUSIANA, LURY SEVITA; MAYADEWI, NI NYOMAN ARI (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016, 2016)
ABSTRACT Cultural Tourism Interpretation Development For Supporting Archeological Site In Preservation Program The development of the archaeological site into a tourist site resulting in the reduction or even loss of the values of the cultural heritage of archaeological objects and the archaeological site. However, the use for tourism can provide economic opportunities to the society and archaeological site preservation. Consequently, there are need some plan that can provide a variety of benefits and economic opportunities and remain to preserve their cultural values. The research aims were to study a variety of solutions and stages for the development of the site for tourism and archaeological interpretation. By looking at the physical, social, cultural, and visual conditions of the site were able to present the potential for tourism development. Analysis and synthesis methods were done to address the various challenges in developing the site. The results of the study was a site plan and a set of development program of the site with interpretation of education-based tourism as a solution for the preservation for the archaeological site. Keywords : archeology site, cultural tourism, interpretation base on education, preservation program